How women living with HIV in the UK manage infant-feeding decisions and vertical transmission risk - a qualitative study - Bakita Kasadha; Lisa Hinton; Shema Tariq; Farai Nyatsanza; Angelina Namiba; Nell Freeman-Romilly; Tanvi Rai (BMC, 2024)
Abstract Background The World Health Organization (WHO) recommends that women with HIV breastfeed for a minimum of one year. In contrast, across high-income countries, HIV and infant-feeding guidelines recommend exclusive formula feeding if parents want to avoid all risk of postpartum transmission. However, recently these guidelines (including in the United Kingdom (UK)) increasingly state that individuals with HIV should be supported to breast/chest feed if they meet certain criteria; such as an undetectable maternal HIV viral load and consent to additional clinical monitoring. Between 600 and 800 pregnancies are reported annually in women with HIV in the UK, with low rates of vertical transmission (0.22%). Informed infant-feeding decision-making requires clinical support. Currently, little research addresses how individuals with HIV in high-income countries navigate infant-feeding decisions with their clinical teams and familial and social networks, and the resources needed to reach an informed decision. Methods Semi-structured remote interviews were conducted between April 2021 - January 2022 with UK-based individuals with a confirmed HIV diagnosis who were pregnant or one-year postpartum. Using purposive sampling, pregnant and postpartum participants were recruited through NHS HIV clinics, community-based organisations and snowballing. Data were analysed thematically and organised using NVivo 12. Results Of the 36 cisgender women interviewed, 28 were postpartum. The majority were of Black African descent (n = 22) and born outside the UK. The majority of postpartum women had chosen to formula feed. Women's decision-making regarding infant-feeding was determined by (1) information and support; (2) practicalities of implementing medical guidance; (3) social implications of infant-feeding decisions. Conclusion The evolution of UK HIV and infant-feeding guidelines are not reflected in the experiences of women living with HIV. Clinicians' emphasis on reducing the risk of vertical transmission, without adequately considering personal, social and financial concerns, prevents women from making fully informed infant-feeding decisions. For some, seeking advice beyond their immediate clinical team was key to feeling empowered in their decision. The significant informational and support need among women with HIV around their infant-feeding options must be addressed. Furthermore, training for and communication by healthcare professionals supporting women with HIV is essential if women are to make fully informed decisions.